2018
DOI: 10.1108/dpm-12-2017-0303
|View full text |Cite
|
Sign up to set email alerts
|

The nature and characteristics of Japanese NGOs in international disaster response

Abstract: Purpose The purpose of this paper is to review the nature of Japanese non-governmental organisations (NGOs) in international disaster response and analyzes their distinctive characteristics. Design/methodology/approach A literature review was conducted of secondary English and Japanese sources including peer-reviewed journals, books, and non-academic journals published by government and NGOs. Findings First, Japanese disaster response NGOs are relatively young compared to Western ones and they continue to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…When other academic projects have looked at volunteers, they have typically used ethnographic and qualitative methods (Nakano, 2000; McMorran, 2017), often focusing on the relationship between the state and volunteerism (Rausch, 2009; Ogawa, 2012). Much of the English literature examines the dynamism of Japan's civil society and its non‐governmental organisations (NGOs), which utilise broader concepts of voluntarism than disaster relief activities (Hirata, 2002; Schwartz and Pharr, 2003; Shaw and Goda, 2004; Pekkanen, 2006; Ogawa, 2009; Kim, 2010; Atsumi and Goltz, 2014; Okada et al, 2017; Iizuka, 2018). These scholars emphasise the structure of civil society rather than the spontaneous goodwill shown by ordinary citizens or groups (Pekkanen, 2003, 2006; Kim, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…When other academic projects have looked at volunteers, they have typically used ethnographic and qualitative methods (Nakano, 2000; McMorran, 2017), often focusing on the relationship between the state and volunteerism (Rausch, 2009; Ogawa, 2012). Much of the English literature examines the dynamism of Japan's civil society and its non‐governmental organisations (NGOs), which utilise broader concepts of voluntarism than disaster relief activities (Hirata, 2002; Schwartz and Pharr, 2003; Shaw and Goda, 2004; Pekkanen, 2006; Ogawa, 2009; Kim, 2010; Atsumi and Goltz, 2014; Okada et al, 2017; Iizuka, 2018). These scholars emphasise the structure of civil society rather than the spontaneous goodwill shown by ordinary citizens or groups (Pekkanen, 2003, 2006; Kim, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Congregations are often among the first organizations to respond during and after disasters (Gajewski et al, 2011; Pant et al, 2008; Provenzo & Provenzo, 2002; Smith & Sutter, 2013) and provide both immediate services and long‐term recovery aid (Bolin & Bolton, 1986; Cain & Barthelemy, 2008; De Vita & Kramer, 2014; Holcombe, 2007; Homeland Security Institute, 2009; Pant et al, 2008; Rivera & Nickels, 2014; Smith & Sutter, 2013). FBOs outside of the immediate area may also support relief efforts through fundraising efforts (Iizuka, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hillig and Connell ( 2018 ) found that network sustainability depended heavily on past practice, NGO member expertise, and the ability to mobilize social capital (Hillig and Connell 2018 ). For example, a case from the NGO Japan Platform (JPF), an international emergency humanitarian aid organization, found that capacity building was vital for efficient joint NGO alliance emergency assistance (Iizuka 2018 ). Similarly, Peng and Wu ( 2018 ) found that substantially improved capacity and professionalism significantly contributed to cross-regional “joint relief operations,” which confirmed that empowering NGOs and enhancing their capabilities was essential for network competence and sustainability (Izumi and Shaw 2012 ).…”
Section: Key Ngo Network Sustainability Factorsmentioning
confidence: 99%
“…NGOs play a vital role in global disaster relief (Kapucu 2007 ). For example, when the 1995 Kobe earthquake struck, hundreds of NGOs joined the relief and reconstruction efforts (Iizuka 2018 ), in the 2008 Wenchuan earthquake, NGOs provided invaluable relief and reconstruction assistance (Xu et al 2017 ), and in the 2010 Haiti earthquake, there was a massive NGO response (Kirsch et al 2012 ). However, when these NGOs flood into disaster areas, they face challenges that often limit the roles they can play.…”
Section: Introductionmentioning
confidence: 99%